Nomogram for predicting the distal adding-on phenomenon in severe and rigid scoliosis - Li, Zhongyang; Yang, Huiliang; Zhou, Chunguang; Xiu, Peng; Yang, Xi; Wang, Lei; Feng, Ganjun; Liu, Limin; Song, Yueming (Frontiers in Surgery, 2023)
Background: The distal adding-on phenomenon has attracted extensive discussion in the field of spine surgery due to the continual occurrence after scoliosis correction. Previous work has mainly focused on adolescent idiopathic scoliosis (AIS), and a relatively high number of theories for the mechanism of the distal adding-on phenomenon has been proposed. Severe and rigid scoliosis, as a special disease form, has a unique etiology, clinical manifestations and internal mechanisms distinct from those of AIS. Given the uniqueness of this disease, the mechanism and causes of the distal adding-on phenomenon have been infrequently studied in depth. Objective: To define clinical and radiological factors associated with distal adding-on in patients with severe and rigid scoliosis. Methods: Radiographic parameters and demographic data of patients with severe and rigid scoliosis were evaluated preoperatively, after posterior instrumentation and fusion surgery, and at the final follow-up via radiographs. According to the appearance of distal adding-on at the final follow-up, the patients were grouped into the Adding-on and the Non-adding-on groups. Various radiological parameters were analyzed in stepwise multivariate logistic regression to identify the variables associated with distal adding-on, which were then incorporated into a nomogram. The predictive performance and calibration of the nomograms for distal adding-on were assessed using C statistics and calibration plots. Results: 93 patients (21 in the Adding-on and 72 in the Non-adding-on group) were included. The incidence of distal adding-on was 22.6%. The variables associated with distal adding-on were the anterior release, posterior internal distraction, and later posterior spinal fusion (IP) procedure, the posterior vertebral column resection and posterior spinal fusion (PVCR) procedure, postoperative apical vertebral translation (Post-AVT) and preoperative slope of the line linking the pedicles on the concave side of the upper- and lower-end vertebrae (Tan α). Combining these factors, the nomogram achieved a concordance index of 0.92 in predicting distal adding-on and had well-fitted calibration curves. Conclusions: For patient with a negative Tanα in severe and rigid scoliosis, the risk of distal adding-on tended to increase, and it is recommended to give priority to IP or PVCR. In the final correction, a smaller Post-AVT should not be pursued excessively.